Mitogen‐activated protein kinase activity drives cell trajectories in colorectal cancer. Issue 10 (19th August 2021) - Uhlitz, Florian; Bischoff, Philip; Peidli, Stefan; Sieber, Anja; Trinks, Alexandra; Lüthen, Mareen; Obermayer, Benedikt; Blanc, Eric; Ruchiy, Yana; Sell, Thomas; Mamlouk, Soulafa; Arsie, Roberto; et al.
Abstract: In colorectal cancer, oncogenic mutations transform a hierarchically organized and homeostatic epithelium into invasive cancer tissue lacking visible organization. We sought to define transcriptional states of colorectal cancer cells and signals controlling their development by performing single‐cell transcriptome analysis of tumors and matched non‐cancerous tissues of twelve colorectal cancer patients. We defined patient‐overarching colorectal cancer cell clusters characterized by differential activities of oncogenic signaling pathways such as mitogen‐activated protein kinase and oncogenic traits such as replication stress. RNA metabolic labeling and assessment of RNA velocity in patient‐derived organoids revealed developmental trajectories of colorectal cancer cells organized along a mitogen‐activated protein kinase activity gradient. This was in contrast to normal colon organoid cells developing along graded Wnt activity. Experimental targeting of EGFR‐BRAF‐MEK in cancer organoids affected signaling and gene expression contingent on predictive KRAS/BRAF mutations and induced cell plasticity overriding default developmental trajectories. Our results highlight directional cancer cell development as a driver of non‐genetic cancer cell heterogeneity and re‐routing of trajectories as a response to targeted therapy. SYNOPSIS: Colorectal cancer (CRC) cells can adopt a range of transcriptomic states. This study uses single cell RNA sequencing of primary CRC tissue and organoids to identify patient‐overarching CRC cell transcriptome clusters. RNA metabolic labelling indicates preferred CRC cell developmental trajectories. CRC cells of multiple patients clustered into six groups – termed TC1‐4, Goblet‐like, and stem‐like – characterized by differential transcriptional footprints of oncogenic signaling pathways. CRC organoid cells develop along a decreasing MAPK gradient. Experimental targeting of EGFR‐MAPK in CRC organoids re‐routes developmental trajectories. Clinically relevant inhibition of EGFR‐MAPK can result in preferential CRC cell development towards endpoints expressing high levels of stem cell markers. Abstract : Colorectal cancer (CRC) cells can adopt a range of transcriptomic states. This study uses single cell RNA sequencing of primary CRC tissue and organoids to identify patient‐overarching CRC cell transcriptome clusters. RNA metabolic labelling indicates preferred CRC cell developmental trajectories.